2018
DOI: 10.1371/journal.pone.0207701
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of interventions for acute diarrhea and gastroenteritis in children: A systematic review and network meta-analysis

Abstract: BackgroundMany interventions have shown effectiveness in reducing the duration of acute diarrhea and gastroenteritis (ADG) in children. Yet, there is lack of comparative efficacy of interventions that seem to be better than placebo among which, the clinicians must choose. Our aim was to determine the comparative effectiveness and safety of the pharmacological and nutritional interventions for reducing the duration of ADG in children.MethodsData sources included Medline, Embase, CENTRAL, CINAHL, LILACS, and Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 66 publications
0
73
1
3
Order By: Relevance
“…To optimise the presentation of results for the 17 diet (14 popular, three control) network meta-analysis, we applied a new approach to summarise the results, establishing different groups of interventions (from the most to the least effective) based on the effect estimates obtained from the meta-analysis and their certainty of evidence 33. For each outcome, we created three groups of interventions.…”
Section: Methodsmentioning
confidence: 99%
“…To optimise the presentation of results for the 17 diet (14 popular, three control) network meta-analysis, we applied a new approach to summarise the results, establishing different groups of interventions (from the most to the least effective) based on the effect estimates obtained from the meta-analysis and their certainty of evidence 33. For each outcome, we created three groups of interventions.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, malaria is caused by protozoa of the genus plasmodium specie and transmitted by female anopheles mosquito [55,56]. Diarrhea and gastroenteritis are mainly caused by rotavirus, norovirus, Salmonella, E. coli, campylobacter and others [57]. The above listed diseases are mostly preventable via simple and less cost effective measures.…”
Section: Plos Onementioning
confidence: 99%
“… 4 However, the effects of probiotics in specific indications are largely strain-dependent and clinical studies designed to evaluate the comparative effectiveness of different probiotic strains are lacking. In a systematic review and network meta-analysis 12 designed to compare and determine the most effective interventions in reducing diarrhea duration, S. boulardii associated with zinc supplementation has been shown superior to both standard treatment, zinc supplementation alone or supplementation with any of the other probiotic strains tested. This finding is notably supported by clinical studies that have compared the efficacy of S. boulardii with lactic acid bacteria or with Bacillus clausii and which have reported positive results in favor of S. boulardii.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, recent clinical studies have found no benefit of probiotics on the duration of diarrhea. 10 , 11 A systematic review and network meta-analysis 12 designed to compare and determine the most effective pharmacologic or nutritional interventions in reducing diarrhea duration supports the recommendation towards the use of S. boulardii in the management of acute diarrhea in children. S. boulardii associated with zinc supplementation has been shown superior to both standard treatment, zinc supplementation alone or supplementation with any of the other probiotic strains tested.…”
mentioning
confidence: 92%